SOSIALISASI, EDUKASI SERTA BAKTI SOSIAL DALAM GERAKAN PESISIR REDAM ABRASI DI PANTAI NAGA PERMAI GAMPONG SUAK PUNTONG KECAMATAN KUALA PESISIR KABUPATEN NAGAN RAYA - Nabil Zurba; Neneng Marlian; Friyuanita Lubis; Mira Mauliza Rahmi; Rinawati Rinawati; Mohammad Gazali (Universitas Teuku Umar, 2021)
One of the most visited tourist attractions in Nagan Raya Regency is the Naga Permai beach area. The beautiful natural panorama makes the Naga Permai beach area a tourist attraction. The high number of tourists is inversely proportional to the quality of the coastline which is increasingly being eroded by abrasion, so more efforts are needed from the local government and also the community in protecting the coast from the threat of increasingly severe abrasion. The purpose of this activity is to provide socialization about the importance of managing coastal areas from the threat of large waves and fast coastal currents, as well as to provide an overview and consequences that will arise in the future if large waves and heavy currents are not anticipated and watched out for and provide direct examples to the community on how to maintain coastal areas in order to reduce the impact of abrasion. This service will be carried out using an approach method with lectures / mentoring. While the steps to solve these problems are by doing examples of social service. The output obtained is the emergence of awareness and initiative from café owners and visitors to maintain and preserve the shoreline from abrasion.